2022
DOI: 10.3390/healthcare10010115
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hygiene Practice among Hospitalized Patients: An Assessment by Dental Hygiene Students

Abstract: Aim: An epidemiological study was carried out, in hospital wards, with the aim of assessing the oral health status of patients subjected to multiple medical treatments. Material and Methods: The study was conducted at Fondazione IRCCS Policlinico San Matteo (Pavia, Italy). A questionnaire was submitted to patients for the evaluation of oral hygiene devices used; then, a clinical examination was conducted to collect Decayed Missing Filled Teeth (DMFT) index, Plaque Index (PI), and Marginal Gingival Index (MGI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…This result suggests that dental students, despite studying for more years and taking more courses on the topic, did not always show significantly better knowledge about DDE than dental hygiene students. This finding underlines the importance of the role that dental hygienists, as competent and qualified health professionals, play within a dental team,, as previously reported [ 33 ].…”
Section: Discussionsupporting
confidence: 82%
“…This result suggests that dental students, despite studying for more years and taking more courses on the topic, did not always show significantly better knowledge about DDE than dental hygiene students. This finding underlines the importance of the role that dental hygienists, as competent and qualified health professionals, play within a dental team,, as previously reported [ 33 ].…”
Section: Discussionsupporting
confidence: 82%
“…In general, medical specialists need to be aware of the periodontal status of their patients, not only at the outpatient clinic. One particular study showed that the presence of gingival index, plaque index and gingival inflammation is high among hospitalized patients across various wards, including the internal medicine infirmary [ 61 ]. In addition, limited knowledge of using dental aids within this group was observed [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…One particular study showed that the presence of gingival index, plaque index and gingival inflammation is high among hospitalized patients across various wards, including the internal medicine infirmary [ 61 ]. In addition, limited knowledge of using dental aids within this group was observed [ 61 ]. Oral health will improve through dental and oral hygienist visits, also by stimulating the use of correct therapeutics; for example, using an electric toothbrush, fluoridated toothpaste and interdental aids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of an electric toothbrush, gels and mouthwashes with an antimicrobial character, and also improving the quality of food, can reduce the plaque deposits and prevent bacterial gingivitis and further complications. In the case of institutionalized children, this help must come from the caregivers or volunteers who are visiting the orphanages and offer their time to educate and teach the children the importance of oral hygiene [ 48 ].…”
Section: Discussionmentioning
confidence: 99%